Evaluación en la aplicación de agregados (ácido cítrico y ascórbico) en la última etapa de desamargado del chocho (Iupinus Mutabilis Sweet) para el empaque en la cooperativa de producción “COOPGRANACH” en la provincia de Cotopaxi, cantón Sigchos , parroquia Chugchilan (2022-2023). - Tituaña Orquera, Yulissa Lizbeth (2023)
In the present investigation, an evaluation of aggregates (citric and ascorbic acid) was carried out in different dosages, the same one that was carried out in the COOPGRANACH processing plant to have a longer useful life of the lupine after packaging, this was carried out with guides in based on the INEN Standard and the CODEX Food Standard, which defines the limit of application of acids based on a Regulation for the use of Additives with parameters for the application of acid on food must be carried out in an amount no greater than the raw material. The application of the acids was carried out through 3 treatments in which different dosages were made, in treatment 1 citric acid was applied in an amount of 25gr in an amount of 600 gr of lupine, in treatment 2 ascorbic acid was applied in an amount of 25gr in an amount of 600gr of lupine and treatment 3 the application of the mixture of the two acids was carried out: citric acid in a concentration of 12.5gr and ascorbic acid with a concentration of 12.5gr with a rest time of 5 minutes and recording the pH data before and after its application, a completely random design was carried out which represents the results. Physical analyzes were carried out where the results that the lupine after 21 days after the application its humidity of lupine without salt is 72.23% and lupine with salt is 72.03% is adequate according to the NTE INEN 2390:2004 Leguminous Standard . Debittered lupine grain. The sensory analysis was carried out based on a completely randomized design (DCA) where the data (color, taste, smell and appearance) was recorded at the time of the design application, it was concluded that all are factors that influence the the lifespan of the pussy. The microbiological analyzes that were carried out (Counts of total mesophilic aerobics, total coliforms, Escherichia coli, mold and yeast) are in a moderate range. The total costs are the adequate ones that can be used in the company to have a previous application in the raw material and be tasted for the market.